Crystal structure of 2-amino-4-(3,5-ditrifluoromethylphenyl)-3-cyano-7,7-dimethyl-5-oxo-4H-5,6,7,8-tetrahydrobenzo[b]pyran, C20H16F6N2O2 - Liu Zhi-Jun (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C6H25Br3N2O3P2, triclinic, P1̅ (No. 2), a = 8.6192(6) Å, b = 10.0012(11) Å, c = 12.8047(8) Å, α = 110.699(8)°, β = 95.859(6)°, γ = 99.141(7)°, V = 1004.36(15) Å3, Z = 2, Rgt(F) = 0.0777, wRref(F2) = 0.1918, T = 293(2) K.